Host-Dependent Differences in Replication Strategy of the Sulfolobus Spindle-Shaped Virus Strain SSV9 (a.k.a., SSVK1): Infection Profiles in Hosts of the Family Sulfolobaceae - Ceballos, Ruben Michael; Drummond, Coyne Gareth; Stacy, Carson Len; Padilla-Crespo, Elizabeth; Stedman, Kenneth Mark (Frontiers in Microbiology, 2020)
The Sulfolobus Spindle-shaped Virus (SSV) system has become a model for studying thermophilic virus biology, including archaeal host-virus interactions and biogeography. Several factors make the SSV system amenable to studying archaeal genetic mechanisms (e.g., CRISPRs) as well as virus-host interactions in high temperature acidic environments. First, it has been shown that endemic populations of Sulfolobus, the reported SSV host, exhibit biogeographic structure. Second, the acidic (pH<4.5) high temperature (65-88°C) SSV habitats have low biodiversity, thus, diminishing opportunities for host switching. Third, SSVs and their hosts are readily cultured in liquid media and on gellan gum plates. Fourth, given the wide geographic separation between the various SSV-Sulfolobus habitats, the system is amenable for studying allopatric versus sympatric virus-host interactions. Previously, we reported that SSVs exhibited differential infectivity on allopatric versus sympatric hosts. We also noticed a wide host range for virus strain SSV9 (a.k.a., SSVK1). For decades, SSVs have been described as “non-lytic” double-stranded DNA viruses that infect species of the genus Sulfolobus and release virions via budding rather than host lysis. Here, we show that SSVs infect hosts representing more than one genus of the family Sulfolobaceae and SSV9 virion release results in lysis of the infected cells. While SSV9 appears to lyse allopatric hosts, on a single sympatric host, SSV9 exhibits canonical non-lytic viral release historically reported SSVs. Thus, the nature of SSV9 lytic-like behavior may be driven by allopatric evolution. The SSV9-infected host growth profile does not appear to be driven by multiplicity of infection (MOI). Greater stability of SSV9 versus other SSVs (i.e., SSV1) in high temperature, low pH environments may contribute to higher transmission rates. However, neither higher transmission rate nor relative virulence in SSV9 infection seems to alter replication profile in susceptible hosts. Although it is known that CRISPR-Cas systems offer protection against viral infection in prokaryotes, CRISPRS are not reported to be a determinant of virus replication strategy. The mechanisms underlying SSV9 lytic-like behavior remain unknown and are the subject of ongoing investigations. These results suggest that genetic elements, potentially resulting from allopatric evolution, mediate distinct virus-host growth profiles of specific SSV-host strain pairings.